A randomized controlled trial to evaluate the laxative effect of prescribed diet compared with Triphala Churna in Vibandha with special reference to constipation - Pooja Saini; Sarvesh Kumar Agrawal (Wolters Kluwer Medknow Publications, 2022)
Introduction: Constipation is a common gastrointestinal complaint in apparently healthy population as well as in patients with various predisposing disorders with approximately 12%-19% global prevalence. Constipation is defined as "delay or difficult defecation causing significant distress to the patient." In Ayurveda, various clinical conditions such as Krurakoshtha, Apanavayudusti, Vishtabdhajirna, Grahani have symptom of constipation called Vibandha. The presently available laxative drugs are habit-forming and financial burden to the patients. Treatment of constipation cannot be continuing for a longer period; therefore, it is a better option to put the patient on proper diet having laxative action in the condition of constipation. The objective of this work is to prepare a dietary module for patient of constipation and to evaluate the laxative effect of that prescribed dietary module (Pathyahara) in constipation. Methods: This study was conducted in two groups. Group A (Control): 3-6g (½ Karsh) Triphala Churna was given orally at night after meal daily with lukewarm water. Group B (Trial): Prescribed Dietary Module was advised as a daily diet. Results: Very significant result was found in both groups on all assessment parameters except weekly frequency of bowel movements in which result was significant in group A and no significant difference was there in all assessment parameters except weekly frequency of bowel movements and colic pain where the effect was more in Group B. Conclusion: Triphala Churna and prescribed dietary module having laxative effect in constipation. The effect was statistically more in prescribed dietary group on two parameters.